Relevance of Baldrige constructs in an international context: A study of national culture - Flynn, Barbara B.; Saladin, Brooke (Journal of Operations Management, 2006)
AbstractBecause of the wide acclaim received by the Malcolm Baldrige Award, it has served as a model for national quality awards by many countries throughout the world. Some countries have adopted both the MBNQA criteria and weights, while others have adapted the criteria categories or weights somewhat. The relevance of this conceptual framework across national cultures has yet to be established, despite its use as the foundation for numerous national quality awards. This study uses Hofstede's dimensions of national culture to examine whether the theoretical constructs underlying the Baldrige criteria are relevant across national cultures. Correlation analysis, stepwise regression and analysis of variance are used to analyze hypotheses in manufacturing plants in the U.S., Japan, Germany, Italy and England. There were many interactions between dimensions of national culture and the Baldrige constructs advanced in this study. The findings indicate that national culture plays a strong role in the effectiveness of the Baldrige constructs, with the exception of customer and market focus. The findings are interpreted in light of the need for countries to develop awards and quality initiatives tailored to their national cultures.